Trichoderma spp: propagación, dosificación, aplicación en el cultivo de maíz (zea mays l) - Cuenca Sedamanos, John Alberto (Machala : Universidad Técnica de Machala, 2022)
The use of Trichoderma spp. is very important for organic agriculture, due to its different mechanisms of action such as the elaboration of secondary metabolites that induce the production of phytoalexins, its antagonistic and antibiosis capacity, which degrades the cell walls of the pathogen. The research was developed at the Technical University of Machala, Faculty of Agricultural Sciences, in the experimental farm "Santa Inés", Machala - El Oro - Ecuador, with the main objective: to determine the effect of different doses of four strains of Trichoderma spp. on agronomic parameters in the maize crop. In strain propagation, was used rice crushed and autoclaved as the culture medium due to its high amount of carbohydrates. The Experimental Design was of Blocks Completely at Random, being evaluated 90 plants by treatment, the applied treatments were: T1 Trichoderma asperellum; T2: Trichoderma melanomagna; T3: Trichoderma spirale; T4: Trichoderma reesei in different doses. For the statistical process, a one-factor ANOVA was performed using SPSS 22 software. The results obtained indicate that the most outstanding variables were: plant height 256 cm in T3D2; seed weight 65.1 g in T2D2 and the lowest percentage seed moisture was 26.2 % in T1D1. In conclusion, the treatments with low doses obtained better results for the mentioned variables.
El uso de Trichoderma spp es muy importante para la agricultura orgánica, debido a sus diferentes mecanismos de acción como la elaboración metabolitos secundarios que inducen la producción de fitoalexinas, su capacidad antagonista y de antibiosis, la cual degrada las paredes celulares del patógeno. La investigación se realizó en la Universidad Técnica de Machala, Facultad de Ciencias Agropecuarias, en la granja experimental “Santa Inés”, Machala – El Oro – Ecuador, se planteó el siguiente objetivo; determinar el efecto de diferentes dosis de cuatro cepas de Trichoderma spp sobre parámetros agronómicos en el cultivo de maíz. En la propagación de las cepas se utilizó el arroz crudo triturado y autoclavado como medio de cultivo debido a su gran cantidad de carbohidratos. El Diseño Experimental fue de Bloques Completamente al Azar, evaluándose 90 plantas por tratamiento, los tratamientos aplicados fueron: T1 Trichoderma asperellum; T2: Trichoderma melanomagna; T3: Trichoderma spirale; T4: Trichoderma reesei en diferentes dosis. Para el proceso estadístico se realizó el ANOVA de un factor mediante uso del software SPSS 22. Los resultados obtenidos indican que las variables más destacadas fueron: altura de planta 256 cm en T3D2; peso de semilla 65,1 g en T2D2 y humedad de semilla de menor porcentaje fue de 26,2 % en T1D1. En conclusión, los tratamientos con dosis bajas obtuvieron mejores resultados para las variables mencionadas.
Keywords: MEDIO DE CULTIVO; ANTAGONISMO; ESPORAS; PRODUCCIÓN